Sustainability and Corporate Social Responsibility in Business Strategy: A Case of Nepalese Enterprise - Gurung, Rohan (Nepalese Journal of Finance, 2025)
This study examines the sustainability and corporate social responsibility in business strategy: A case of Nepalese enterprise. Stakeholder’s perception is a dependent variable. The selected independent variables are CSR initiatives, investment, competition, corporate governance, training, and policy adoption. The primary source of data is used to assess the opinions of respondents regarding CSR initiatives, investment, competition, corporate governance, training, policy adoption, and stakeholder’s perception. The study is based on primary data of 125 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of sustainability and corporate social responsibility in business strategy: A case of Nepalese enterprise. The study showed a positive impact of CSR initiatives on stakeholder’s perception. It indicates that increase in CSR initiatives leads to change in the stakeholder’s perception. Similarly, the study showed a positive impact of investment on stakeholder’s perception. It indicates that higher investment leads to understanding of CSR having influence over stakeholder’s perception. Likewise, the study showed a positive impact of competition on stakeholder’s perception. It indicates that both positive competition acts upon the influence over stakeholder’s perception. Further, the study also showed a positive impact of corporate governance on stakeholder’s perception. It indicates that corporate governance enhance trust and credibility, transparency and accountability, ethical conduct which leads shape a crucial role in stakeholder’s perceptions. In addition, the study showed a positive impact of policy adoption on stakeholder’s perception. It indicates that proper integrated policy leads to change in stakeholder’s perception. Moreover, the study showed a positive impact of training on stakeholder’s perception. It indicates that business enterprise’s approach towards training leads to have significant influence over stakeholder’s perception.